1988
DOI: 10.1016/s0006-3495(88)83006-6
|View full text |Cite
|
Sign up to set email alerts
|

The kinetics relating calcium and force in skeletal muscle

Abstract: The kinetics relating Ca2+ transients and muscle force were examined using data obtained with the photoprotein aequorin in skeletal muscles of the rat, barnacle, and frog. These data were fitted by various models using nonlinear methods for minimizing the least mean square errors. Models in which Ca2+ binding to troponin was rate limiting for force production did not produce good agreement with the observed data, except for a small twitch of the barnacle muscle. Models in which cross-bridge kinetics were rate … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
20
0
1

Year Published

1991
1991
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(21 citation statements)
references
References 39 publications
0
20
0
1
Order By: Relevance
“…We assume that r increases to 1 immediately following the firing of an action potential, which is assumed to be very brief (Ͻ1 ms), and decays exponentially with a time constant r . This assumption is based on several studies with skeletal muscles (Miledi et al, 1982;Stein et al, 1988), in which intracellular Ca 2ϩ transients, in response to repetitive action potentials, exhibited sublinear processes. The value of r (fraction of open RyRs) between spikes k and k ϩ 1 is therefore…”
Section: Methodsmentioning
confidence: 99%
“…We assume that r increases to 1 immediately following the firing of an action potential, which is assumed to be very brief (Ͻ1 ms), and decays exponentially with a time constant r . This assumption is based on several studies with skeletal muscles (Miledi et al, 1982;Stein et al, 1988), in which intracellular Ca 2ϩ transients, in response to repetitive action potentials, exhibited sublinear processes. The value of r (fraction of open RyRs) between spikes k and k ϩ 1 is therefore…”
Section: Methodsmentioning
confidence: 99%
“…It was assumed, for simplicity, that the muscle contraction is limited by calcium kinetics, namely that Ca 2 diffusion in the cytoplasm and acto-myosin cross-bridge formations are rapid and not acting as rate limiting factors [36]- [38]. The active state of the muscle was thus expressed by the following two dynamic variables: a) Ca 2 concentration: The temporal intracellular (myoplasm) free concentration of Ca 2 ions, [Ca] , is governed by the release and uptake of calcium from and into the SR.…”
Section: ) the Musculotendon Modelmentioning
confidence: 99%
“…If there is no cooperativity between the sites, then the reaction between calcium and troponin is modeled by the following first-order reaction [38]: (10) given by the differential equation: The rate constants and express respectively, the forward and backward Ca 2 -troponin kinetics [37], [38]. It was shown that force production is proportional to the number of Ca 2 ions bound to each troponin molecule [38], hence, , and with . The parameters used in (9) and (11) are given in Table II [41], [42].…”
Section: ) the Musculotendon Modelmentioning
confidence: 99%
See 1 more Smart Citation
“…[Japanese Journal of Physiology, 52, [479][480][481][482][483][484][485][486][487]2002] [ [16][17][18]. Twitch tension, generated by direct electrical stimulation, depends on interactions between different processes mentioned above and any change in the developed tension could be related to changes in the different steps of the excitation-contraction coupling mechanism [19,20]. However, in order to look at excitation-contraction coupling directly, without complications of additional effects due to the action potential, potassium (K ϩ ) contracture was generally used rather than twitch tension response.…”
mentioning
confidence: 99%